Contrasting first- and second-order electoral behaviour: determinants of individual party choice in European and German Federal elections - Heiko Giebler; Aiko Wagner (German politics, 2015)
In contrast to national elections, both parties and voters are assumed to think that `less is at stake' in European elections: Campaigns are less intense, turnout is lower, and citizens are more inclined to `vote with their hearts'. The latter should be reflected in differing rationales of voting – party choice should not be based on identical determinants in national and European elections. However, this hypothesis has not been sufficiently tested and most of the research is based on the analysis of aggregated data while causal explanations are located on the micro level. This paper compares vote functions of individuals in regard to the 2009 European Parliament election as well as the 2009 German Federal election. Using data from the German Longitudinal Election Study (GLES), comparison of explanatory models shows that party choice on both levels is neither fundamentally different nor does it fit into the pattern of second-order electoral behaviour.
Additional information: Accepted version (postprint) / Akzeptierte Manuskriptfassung (postprint)
Keywords: 330; Wahlverhalten; Wähler; Determinanten; Partei; Präferenz; Europawahl; Bundesrepublik Deutschland; Wahlbeteiligung; Parlamentswahl; Bundestagswahl